Drug-induced oedema - Schindler, C.; Schellong, S. M. (Phlebologie, 2009)
Besides more classical aetiologies for oedema such as heart failure, liver cirrhosis, nephrotic syndrome and chronic venous insufficiency, in practice we increasingly observe iatrogenic or drug-induced oedema as adverse events. Many drugs have the potential to cause oedema or to worsen pre-existing oedema prior to the initiation of drug therapy. Drug-induced oedema is frequently caused by calciumchannel-blockers of the dihydropyridine-type but can also be caused by dihydralazine and minoxidil which are less frequently prescribed. Other drugs which may support the formation of oedema are diuretics, nonsteroidal anti-inflammatory drugs (NSAIDs), ACE-inhibitors or AT1-receptor-antagonists (angioedema) and thiazolidinediones/glitazones which are used as oral anti-diabetics.This review focuses on drug-induced oedema, pathophysiological considerations and potential treatment and management strategies from a clinical-pharmacological perspective.
Keywords: Drug-induced oedema; vasodilators; calcium channel blockers; loop-diuretics; ACE-inhibitors; AT1-receptor-blockers; glitazones; pathophysiology; treatment strategies